If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 3z + -5 Reorder the terms: 1 = -5 + 3z Solving 1 = -5 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 1 + -3z = -5 + 3z + -3z Combine like terms: 3z + -3z = 0 1 + -3z = -5 + 0 1 + -3z = -5 Add '-1' to each side of the equation. 1 + -1 + -3z = -5 + -1 Combine like terms: 1 + -1 = 0 0 + -3z = -5 + -1 -3z = -5 + -1 Combine like terms: -5 + -1 = -6 -3z = -6 Divide each side by '-3'. z = 2 Simplifying z = 2
| -18-65n+-42=-60 | | -34=4x-6x-10 | | -11-10(p+10)=4-5(2p+23) | | y-5.99x=-2 | | 7=2r+1 | | 6=-x+2x-5 | | 8-3v=3v+2 | | -x+8-3x=-36 | | 13-2v=9 | | 6=2+2n | | a+2b=30 | | 2x+49=7(x+7)-5x | | -2w=-5(w-6) | | 7x-7+4x=15 | | (u-7)*9=45 | | -(z+6)+(6z+1)=4(z+1) | | 3x+12+4x+8=27 | | -6(x+7)=2x+38 | | 39=2x+4x+9 | | .25x+.1(x+3)+.05(2x)=4.65 | | 3(2g-1)=6g-4 | | (q-5)*2=6 | | 39=2x+4x+9x | | -10n+3(8+8n)=-2(n-4) | | z+7=44 | | 8v+28=-3(v-2) | | 19-c=4 | | -7(k+3)-(-8k+7)=5 | | 2+3x-5x=-4 | | 16(x-9)=4(2a-x) | | -6(u+6)=4u+4 | | 1/4t+3/5=2/5-t |